MASLAHAT DALAM HUKUMAN MATI BAGI PELAKU LGBT - Muhammad Taufan Djafri; Darussalam Syamsuddin; Abdul Syatar (Fakultas Syariah Institut Agama Islam Negeri Palu, 2022)
Lesbian, Gay, Bisexual and Transgender (LGBT) is a term used since the 1990s to describe a group of people with different sexual orientations and behaviors. This term replaces the previous phrase